Relationship between Perineal Body Length and Degree of Perineal Tears in Primigravidas Undergoing Vaginal Delivery with Episiotomy - Suskhan Djusad; Yuditiya Purwosunu; Fadil Hidayat (Obstetrics and Gynecology International)
Background. Perineal tears are one of the most common complications of vaginal delivery. Severe perineal tears can cause various morbidities. There are many factors that affect the occurrence of perineal tears. One of the major factors related to the occurrence of perineal tears is the length of the perineal body. However, until now, no research in Indonesia has concluded that the length of perineal body can predict the perineal tears. Objective. To find the relationship between perineal body length and perineal tears, so it can provide a reference on the use of perineal body length to predict severe perineal tears in vaginal delivery with episiotomy. Methods. This nested case-control study was conducted at RSUD Tangerang and RSUD Karawang in Indonesia from February to September 2017. A total of 126 primigravida patients participated in the study consecutively. The length of the perineal body was then measured and followed until the start of the second stage of labor. Afterwards, the perineal length and degree of perineal tears were assessed using unpaired T-test for bivariate analysis, multivariate analysis, and scoring test to predict the occurrence of third- and fourth-degree of perineal tears with power calculation (β) 80% and Zβ 0.842. Results. There was a significant difference in mean length of the perineal body between the group with first- and second-degree perineal tears and the group with third- and fourth-degree perineal tears (p<0.001). From the multivariate analysis, adjusted OR was 5.26 (95% CI 1.52–18.17). Score test was performed to predict the occurrence of third- and fourth-grade perineal tears. Perineal body length and head circumference could be used as predicting factors of perineal tears. Perineum length ≤ 3.0 cm and head circumference ≥ 33.5 cm posed a risk of perineal tears of third and fourth degrees (70.52%). Conclusion. The length of the perineal body has a good ability to predict the occurrence of perineal tears.